PENGARUH KOMPLEKSITAS PERUSAHAAN, CORPORATE GOVERNANCE, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG - Septriani, Yossi; Ramadhea JR , Syafira; Ananta, Raissa Seftiana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Audit report lag refers to the time required to complete the audit process until the publication date of the company's audit report, calculated from the company's fiscal year-end to the date stated in the independent auditor's report. Audit report lag may occur due to several internal and external factors. Therefore, this study aims to examine the influence of company complexity, corporate governance mechanisms, public accounting firm size, and audit opinions on audit report lag. This research employs agency theory. The sample in this study consists of 68 consumer cyclicals companies listed on the Indonesia Stock Exchange from 2018 to 2022, with a total of 272 data points. The sampling technique used is purposive sampling. The data analysis method employed is panel data regression analysis. The results of this study indicate that company complexity has a significant positive effect on audit report lag, while audit opinion has a significant negative effect on audit report lag. Meanwhile, the audit committee, board of commissioners, and public accounting firm size do not affect audit report lag.